Theoretical Semi-Empirical Calculation of Molecular Structure of Schiff Base Complexes Zn (II). - Muala, Adil; Ali, kawkab (University of Thi-Qar Journal of Science, 2011)
Zn-Schiff-base Complexes(II) have been synthesized. The Schiff-bases prepared and theircomplexes were identified by IR, UV-Visible and elemental analysis (CHN). These experimentsshow that transition metal can form complexes with Schiff base in the ratio 1:2[M:L]. TheSchiff-base(I,II) and their complexes(III,IV) were studied by quantum chemical methods, theoptimized structures of the compounds(I,II,III,IV) were obtained by the semi-empirical PM3method. The value of total energy for complexes as found (III,IV) is less than Schiff base ligand (I,II), which strongly indicates the stability of the complexes. Also the dipole moment of complexes high values as compared with Schiff base ligand. The changes of the bond lengths in complex (IV) indicate the presence of π-conjugation in the aromatic system for aromatic ligand (II) if compared with aliphatic ligand(I). The mean distances N-Zn and O-Zn in the complex(IV) an decreased compared with the complex (III))because of the complex (IV) have high electrostatic attraction.